Compendium of key human rights documents of the African Union - Fourth Edition - Magnus Killander (Pretoria University Law Press (PULP), 2010)
About the publication This is the fourth edition of the Compendium of key human rights documents of the African Union updated to August 2010. This Compendium contains documents on human rights adopted under the auspices of the African Union (AU) and its predecessor, the Organization of African Unity (OAU), including documents adopted by the African Commission on Human and Peoples' Rights, the African Court on Human and Peoples' Rights and those relating to the African Peer Review Mechanism (APRM) of the New Partnership for Africa's Development (NEPAD). The earlier editions of the Compendium have been used widely by judges, lawyers, civil servants, NGOs and academics alike, in Africa and abroad, who have an interest in the African human rights system. Many of the documents reprinted here are also available in the reference work Human Rights Law in Africa (2004), edited by Christof Heyns and Morné van der Linde, and the African Human Rights Law Reports. These two publications contain many more sources than are reprinted here. For comprehensive coverage of human rights law in Africa and for updates on this material, see www.chr.up.ac.za. The titles of documents used in the table of contents have in many cases been abbreviated; the full titles are used as headings in the text. This Compendium was compiled at the Centre for Human Rights, with Christof Heyns and Magnus Killander as editors, with the assistance of Frans Viljoen. The assistance of Karen Stefiszyn, and Michelo Hansungule in the compilation of previous editions is gratefully acknowledged. Lizette Besaans formatted the document, supervised the production process and held the whole project together. The organogrammes of the AU were compiled by Karen Stefiszyn and Magnus Killander. Yolanda Booyzen provided IT assistance. Lizette Besaans is the manager of PULP. We are most grateful to Ms Julia Joiner, Commissioner for Political Affairs of the AU, for her warm encouragement and support for this publication, as is reflected in the foreword. This publication was supported by the Raoul Wallenberg Institute of Human Rights and Humanitarian Law. The 2010 edition of the Compendium will also be available in French. An earlier edition is also available in Arabic and Portuguese. Compendium of key human rights documents of the African Union - Fourth Edition Edited by Christof Heyns and Magnus Killander 2010 ISBN: 978-0-9869857-0-6 Pages: ix 485 Print version: Available Electronic version: Free PDF available